Conducta obstétrica ante violencia sexual: embarazo en adolescente de 12 años de edad con anemia severa - Castro Zambrano, Stephanie Carolina (2021)
In Ecuador, thousands of girls and adolescents have suffered sexual violence, it is estimated that in the highest percentage of cases, the victims know their aggressors, since they belong to their closest circles. Pregnancy in adolescents due to sexual violence also results in a lack of care by the future mother towards the fetus. This lack of attention and feeding of the mother, in most cases causes severe anemia. In the case of child abuse, 90% of the victims knew their aggressor beforehand, approximately 40% of sexual assaults occur at the home of the victims and another 20% occur at the home of a friend, of a neighbor or a family member. The general objective of this report is to describe pregnancy and anemia in adolescents due to violence, the specific objectives are to determine risk factors for pregnancy and anemia in adolescents due to violence and to describe the clinical criteria and diagnostic tests for pregnancy and anemia in adolescents due to violence. As part of the research, a case study is attached, which is based on a 12-year-old patient with a diagnosis of 33 weeks 'gestation and 3 days' gestation + severe anemia + sexual violence. The patient reports a clinical picture of more or less 2 days of evolution characterized by weakness, dizziness, pale skin. In the health center where he is attended, a hematic biometry is performed, which results are HB 5.1 g / dl and Hto: 15%. Category I fetal monitoring with fcf: 135 - 140bpm, negative uterine activity, fetal movements present. The immediate admission of the patient for blood transfusion is decided. Sexual violence mainly affects adolescent women, who conceive unwanted pregnancies, which are caused in most cases by people from their family environment.